Analisa Perbandingan Algoritma Elias Gamma Code Dan Algoritma Goldbach Code Pada Kompresi File Dokumen - Ari Pradana (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
In the current Covid-19 era, especially all schools and universities, implementing an online learning system that makes a lot of data needed, one type of data is packaged in a document file with the RTF extension to send information because this file type is quite detailed and flexible in the process. the editing. But sometimes the RTF file has a large data capacity size, so it takes a long time in the data transmission process and results in wasting storage space. Therefore, a data compression technique is needed so that the data size becomes smaller and does not consume a lot of storage space. The compression process can be done with many existing algorithms, in this study the compression process will be carried out with the Elias Gamma Code algorithm and the Goldbach Code algorithm. Which results from the Elias Gamma Code algorithm getting a compression result of 42.5% while the Goldbach Code algorithm gets a compression result of 47.5%. Of the two algorithms there are many advantages and disadvantages of each algorithm, so a comparison process will be carried out between the two algorithms by determining several parameters, namely Ratio of Compression (RC), Compression Ratio (CR), Redundancy (RD), and Space. Savings (SS). From the comparison results, the Goldbach Code algorithm becomes the most effective algorithm for compressing document files with a value of 7,355.